Odpowiedzi

2010-03-13T18:18:05+01:00
A) 1/2x - 4 = x - 6
1/2x - x = -6 + 4
- 3/2x = -2 /-3/2
x = 1 1/3

b) x -5 = 1/3x + 1
x - 1/3x= 1 +5
2/3x = 6 / 2/3
x= 9

c)x/4 - 1/4 = 2 / *4
x - 1 =8
x= 8 +1
x = 9

d) x/5 -3 = x + 1/5 / *5
x -15= 5x + 1
x - 5x = 15 +1
-4x= 16 /-4
x= - 4





18 3 18
Najlepsza Odpowiedź!
2010-03-13T18:18:39+01:00
A)
0,5x-4=x-6
-4+6=x-0,5x
2=0,5x
4=x
b)
x-5=⅓x+1
x-⅓x=1+5
⅔x=6
x=9
c)
x÷4-¼=2
x-1=8
x=9
d)
x√5-3=x+1/5
-3-1/5=x-x√5
-3,2=x(1-√5)
-3,2÷(1-√5)=x
((-3,2*(1+√5))÷-4=x
(-3,2-3,2√5)÷-4=x
-0,8-0,8√5=x
e)
5/6(x-1)=4
5/6x-5/6=4
5/6x=4+ 5/6
5/6x=29/6
x=29/5
x=5,8
f)
-1/2(-x-6)=-x
1/2x+3=-x
1/2x+x=-3
1,5x=-3
x=-2



118 3 118
2010-03-13T18:30:38+01:00
A
1/2x-4=x-6
1/2x-x = -6 +4
-1/2 x+ = -2 / -1/2
x= -2 * (-2)
x=4

b
x-5= 1/3x + 1
1/3x-x= 1+5
-4/3x= 6 / (-4/3)
x=6*(-3/4)
x= - 4 i 1/2

c
x/4 - 1/4= 2
x/4 - 1/4= 2 / *4
4*x/4 - 4*1/4 + 4*2
x-1=8
x= 8+1
x=9

d
x/5 - 3= x+ 1/5 / *5
5* x/5 - 5*3= 5x + 5 * 1/5
x -15= 5x + 1
5x-x= 1+15
4x = 16 /4
x=4

e
5/6[ x-1] = 4 /*6
6* 5/6 [x-1]= 6*4
5[x-1]=24
5x -5= 24
5x= 24 +5
5x= 29 ? 5
x= 29/5
x= 5 i 4/5

f
- 1/2 [ -x-6]= -x /*2
2(-1/2)* [-x-6]= 2*( -x)
-1* [ -x-6]= -2x
x+6= -2x
2x+x= -6
3x= -6 /3
x= -6/3
x= -2


Mam nadzieję, że pomogłam :)

27 3 27